2016
DOI: 10.2300/acari.25.suppl_147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of <i>Euseius gallicus</i> as a biological control agent of western flower thrips and greenhouse whitefly in rose

Abstract: Euseius gallicus is a new phytoseiid species recently described from southern France that has shown potential as a biocontrol agent for thrips and whitefly in rose, if pollen is supplied as an additional food source. To investigate if the use of E. gallicus provides improved thrips and whitefly control, we conducted laboratory experiments examining the biology of E. gallicus and a semi-field experiment comparing the biological control efficiency of E. gallicus with that of Amblydromalus limonicus and Amblyseiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…While the successful use of A. swirskii as a biological control agent for S. dorsalis has been demonstrated (Avery et al, 2014; Kumar et al, 2015), data on the efficacy of A. limonicus were unavailable and the results suggest that it is a promising predator of S. dorsalis . The lack of differences in S. dorsalis populations on plants between mite species treatments in this study aligns with the findings of van Houten et al (2016), who found no difference in the control achieved by A. limonicus and A. swirskii released against F. occidentalis infesting roses. They observed, however, that A .…”
Section: Discussionsupporting
confidence: 92%
“…While the successful use of A. swirskii as a biological control agent for S. dorsalis has been demonstrated (Avery et al, 2014; Kumar et al, 2015), data on the efficacy of A. limonicus were unavailable and the results suggest that it is a promising predator of S. dorsalis . The lack of differences in S. dorsalis populations on plants between mite species treatments in this study aligns with the findings of van Houten et al (2016), who found no difference in the control achieved by A. limonicus and A. swirskii released against F. occidentalis infesting roses. They observed, however, that A .…”
Section: Discussionsupporting
confidence: 92%
“…Van Houten et al (2016) reported that the development time from egg to egg-laying female is affected by temperature. At 13 °C, the development takes 22 days with 1.1 eggs laid/day/ female, while at 25 °C, the development takes 5 days only with 3.6 eggs laid/day/female.…”
Section: Euseius Gallicus Kreiter and Tixiermentioning
confidence: 99%
“…Euseius gallicus Kreiter & Tixier (in Tixier et al 2010) is one of the recently described species, and its natural populations have been reported from a total of 10 countries (Döker et al 2014;Tsolakis & Ragusa 2017;Kreiter & Abo-Shnaf 2020;Farazmand et al 2023;Novljan et al 2023). Most importantly, it had become a commercial product due to its potential as a biocontrol agent of western flower thrips and whiteflies (Pijnakker et al 2014;Van Houten et al 2016). The original description of species is quite detailed with illustrations and more than 100 type specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, it had become a commercial product due to its potential as a biocontrol agent of western flower thrips and whiteflies (Pijnakker et al . 2014; Van Houten et al . 2016).…”
Section: Introductionmentioning
confidence: 99%